Kedudukan Prinsip Kehati-Hatian Terhadap Sifat Perjanjian Baku Dalam Pemberian Kredit Perbankan - Mahdi Surya Aprilyansyah (Belom Bahadat, 2020)
The purpose of this study is to describe the position of the prudential principle towards the nature of standard agreements in the provision of bank credit. The method used is normative juridical by analyzing statutory regulations and library materials systematically in order to provide meaning and answer legal problems. The results of this study suggest that a standard agreement made unilaterally cannot be interpreted as a loss for the debtor, but rather a form of embodiment of the mandate of Law Number 10 of 1998 Article 29 paragraph 3 to avoid losses for the bank and customers.